PENGARUH PROFITABILITAS, STRUKTUR MODAL, UKURAN PERUSAHAAN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN: (Studi Empiris Pada Perusahaan Sektor Teknologi yang Terdaftar di BEI Periode 2021-2023) - Himmah, Faiqotul; Setiyono, Taufiq Andre (Perwira Journal of Economics & Business, 2025)
This study aims to empirically determine and examine the effect of profitability, capital structure, firm size, and company growth on firm value as measured by Tobins’Q. The population in this study are technology sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2021 to 2023, namely 27 companies. This study uses secondary data obtained from the company’s financial statements and this type of research is quantitative research. Determination of the sample using purposive sampling method using certain criteria and obtained 11 technology sector companies are obtained as research samples. The data analysis method used is multiple linear regression analysis using the IBM SPSS version 25 program. The results of this study indicate that profitability measured by Return on Equity (ROE) has a significant positive effect on firm value. Meanwhile, capital structure measured by Debt to Equity (DER) have no effect on firm value. Firm size have no effect on firm value. And company growth have no effect on firm value.